Religious Moderation in Mathematics Learning: A Bibliometric Analysis - Al Kusaeri; Alfira Mulya Astuti; Kristayulita; Erpin Evendi; Muhammad Habib Husnial Pardi; Afifurrahman (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
An urgent issue related to national identity is the promotion of religious moderation, a responsibility shared by all sectors of society. Religious moderation should not be confined to religious education alone, but rather be embedded across all academic disciplines, including mathematics. This study investigates the trends of religious moderation within mathematics education research between 2019 and 2025, employing the bibliometric analysis method. The review focuses on mathematical content, research methodologies, levels of implementation, and country. Data for the study were sourced from Google Scholar, ScienceDirect and Dimensions AI databases. The selected publications were screened using the Systematic Review Accelerator and mapped through the PRISMA framework, based on predefined inclusion criteria. There are 14 (fourteen) articles assessed. Analytical tools included VOSviewer 1.6.20, RStudio-2024.09.0-375, and Microsoft Excel 365. The results reveal two key findings: (1) the concept of fractions is the most frequently associated with religious moderation practices in mathematics classroom, (2) The predominant approach employed by scholars to examine the incorporation of religious moderation in mathematical education is library research, and (3) the integration of religious moderation into mathematics education is primarily observed at the elementary level and is largely limited to the Indonesian context. Therefore, efforts to incorporate religious moderation into mathematics teaching should be expanded across all levels of education.